Painted woodcut of a Harris's Sparrow attached to the exterior wall of the Yellowknife Inn, Yellowknife, NWT. - Campbell, Sandy (2015)
Harris's Sparrow is the largest sparrow in North America and is the only bird that breeds only in northern Canada. This woodcut painting is attached to the corrugated steel south wall of the Yellowknife Inn and is part of a series of artworks installed on this wall. The sparrow is shown perched on a branch. The accompanying sign on the wall reads "Le choix de Suzanne" (Suzanne's choice).